AUTONOMOUS LEARNING AS LANGUAGE LEARNING STRATEGY BASED ON STUDENTS PREFERENCED LEARNING STYLE - Hasanah Uswatun (Institut Agama Islam Negeri Palopo, 2013)
In teaching and learning process, teachers often focus more on how to teach than on how the students learn. Knowing the appropriate learning strategies will able to examine not just how to teach effectively, but what the students do to facilitate their own learning. Chosing appropriate teaching techniques become evidence that learner tend to take more responsibility for their own learning. Autonomous leaning is one way to realize that. In autonomous learning the students are forced to be the independent learners. They can take incharge on their own learningwhich sees learners as individuals who can and should control and be responsible for their own learning climate.One way to apply the autonomus learning is by knowing the students preferenced learning style. There are different learning styles of students. Three of the most popular ones are visual, auditory, and kinaesthetic.